Prognostic Value of Neutrophil–Lymphocyte Ratio, Platelet–Lymphocyte Ratio, and Combined Neutrophil–Lymphocyte Ratio and Platelet–Lymphocyte Ratio in Stage IV Advanced Gastric Cancer - Wang, Huan; Ding, Yongfeng; Li, Ning; Wu, Luntao; Gao, Yuan; Xiao, Cheng; Jiang, Haiping; Zheng, Yulong; Mao, Chenyu; Deng, Jing; Wang, Haiyong; Xu, Nong (Frontiers in Oncology, 2020)
Background: The prognostic value of neutrophil–lymphocyte ratio (NLR), platelet–¬-lymphocyte ratio, and the combined NLR-PLR score in patients with stage IV GC has not been clarified. Therefore, the main aim of this study was to explore the potential association of NLR, PLR, and NLR-PLR score and prognosis in patients with stage IV GC. Methods: This was a retrospective study of 466 GC patients diagnosed between 2010 and 2017. High NLR and high PLR were defined using the median values as the cut-off values. We then combined the NLR and PLR value and generated the NLR-PLR score as a new biomarker. Patients were separated into three parts according on the NLR-PLR score. Univariate and multivariate analyses were conducted to compare survival outcomes. Results: The median overall survival (OS) and progression-free survival (PFS) were 15.5 months (range, 0.7-96.8 months) and 6.7 months (range, 0.5-30.4 months). The NL, PLR and the NLR-PLR score were correlated with clinical outcomes including OS and PFS. The median OS for patients with NLR-PLR scores of 0, 1, and 2 were 22.5, 15.7, and 11.2 months, respectively. The median PFS for patients with NLR-PLR scores of 0, 1, and 2 were 7.8, 7.1 and 5.2 months, respectively (P<0.001). An high NLR-PLR score predicted poor survival time in patients with stage IV GC (all P<0.05). Conclusion: This analysis provides scientific evidence to support that NLR-PLR score may be a pre-treatment factor that independently predicts survival outcomes in GC patients.